2018
DOI: 10.51985/jbumdc2018022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment Of Bonding Agent v/s Fluoride Varnish In Dentinal Hypersensitivity

Abstract: Objective: To compare the mean reduction in pain scores between Bonding agent (GLUMA® Comfort® Bond+ Desensitizer, and Fluoride varnish. Methodology: The study was conducted at Operative Dentistry, Department at Altamash Institute of Dental Medicine, Karachi from July 2015 to August 2016. Total 152 patients were selected. Patients were randomly allocated into two groups A and B. Gluma comfort bond plus desensitizer® was applied to the patients in group A and Duraphet® was applied to the patients in group B. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
3
3
0
Order By: Relevance
“…Consistent with the ndings of this study, Mehta et al (2014) and Ahmed et al (2019) discovered that Gluma exhibited greater effectiveness in alleviating dentine hypersensitivity, and their results indicated a lasting desensitization effect for six months [25]. Also, Gowri and Kannan's research, as illustrated in Table 2, demonstrated that Gluma led to a signi cant reduction in Visual Analog Scale (VAS) ratings after one week, while Duraphat did not [26,27].…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with the ndings of this study, Mehta et al (2014) and Ahmed et al (2019) discovered that Gluma exhibited greater effectiveness in alleviating dentine hypersensitivity, and their results indicated a lasting desensitization effect for six months [25]. Also, Gowri and Kannan's research, as illustrated in Table 2, demonstrated that Gluma led to a signi cant reduction in Visual Analog Scale (VAS) ratings after one week, while Duraphat did not [26,27].…”
Section: Discussionsupporting
confidence: 79%
“…Similarly the significant decrease in dentin hypersensitivity score after dentin bonding agent thereby might be due to occlusion of dentinal tubules due to formation of resin tags. Same results were found in a study conducted by Praveen R et al 13 Ahmed J et al 14 conducted a study to compare dentin bonding agent and fluoride varnish in which dentin bonding agent showed significant reduction in VAS score. Mazur M et al 15 did a study toevaluate the clinical effificacy of a in-office application of a fluoride varnish and a bonding resin.…”
Section: Discussionsupporting
confidence: 64%
“…Other than sugar, there are several other factors that contribute to caries development, including poor oral hygiene, cariogenic bacteria, and saliva volume [ 13 ]. Dental caries causes sensitivity and pulpal pain, which can lead to decline in the academic performance of dental students, loss of teeth, aesthetics problems, and lack of confidence [ 14 , 15 ]. Body mass index (BMI) is a measurement of body fat based on adult men's and women's height and weight.…”
Section: Introductionmentioning
confidence: 99%